MENINGKATKAN KEAKTIFAN DAN PRESTASI BELAJAR PPKn DENGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING KELAS III SD KANISIUS KINTELAN 1 - MONICA SANDRA GITAWATI; MARIA AGUSTINA AMELIA; MARCIANA SARWI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
The learning process should be able to actively involve students and encourage students to seek, and acquire knowledge and knowledge on their own with the guidance of teachers. Teachers are no longer the only source of knowledge for students. Based on observations at SD Kintelan 1 the learning process for Civics material has not been carried out effectively. This can be seen in the activeness of students in the class who tend to be passive in receiving the material resulting in a lack of students' understanding of the material provided. So we need an innovative method to encourage active participation of students in the class to improve learning achievement. This study aims to determine the use of the Problem Based Learning learning model in Civics learning, especially the material for the State Emblem of Indonesia for third-grade students of SD Kanisius Kintelan 1 Yogyakarta so that learning can improve learning achievement and activeness. This study uses a classroom action design that takes learning in class. Based on the distribution of activity observation results and learning achievement test scores at the end of the second cycle, the data shows that the use of the Problem Based Learning learning model increases the activity of third-grade students at SD Kanisius Kintelan 1 from the initial condition, the average activity is 55%, increased by 68% (cycle I), increased to 77% (cycle II) and an increase in student achievement, with the initial average score of 33.7 increasing to 76.00 (cycle I) and increasing to 80.0 (cycle II). ABSTRAK Proses pembelajaran sudah selayaknya dapat melibatkan siswa secara aktif dan mendorong siswa untuk mencari, memperoleh ilmu dan pengetahuannya sendiri dengan bimbingan para guru. Guru bukan lagi menjadi sebagai satu-satunya sumber ilmu pengetahuan bagi peserta didik. Berdasarkan Pengamatan di SD Kintelan 1 proses belajar materi PPKn belum dilakukan secara efektif. Hal ini nampak pada keaktifan siswa dikelas yang cenderung pasif dalam menerima materi mengakibatkan kurangnya tingkat pemahaman siswa terhadap materi yang diberikan. Sehingga diperlukan suatu metode yang inovatif untuk mendorong partisipasi aktif siswa dikelas sehingga dapat meningkatkan prestasi belajar. Penelitian ini bertujuan untuk mengetahui penggunaan model pembelajaran Problem Based Learning dalam pembelajaran PPKn khususnya materi Lambang Negara Indonesia siswa kelas III SD Kanisius Kintelan 1 Yogyakarta agar pembelajaran dapat meningkatkan prestasi belajar dan keaktifan. Penelitian ini menggunakan rancangan tindakan kelas yang mengambil pembelajaran di kelas. Berdasarkan data distribusi hasil observasi keaktifan dan nilai tes prestasi belajar diakhir siklus kedua, data menunjukkan penggunaan model pembelajaran Problem Based Learning meningkatkan keaktifan siswa kelas III SD Kanisius Kintelan 1 dari kondisi awal rerata keaktifan sebesar 55% meningkat sebesar 68% (siklus I), meningkat menjadi 77% (siklus II) dan adanya peningkatan prestasi belajar siswa, dengan nilai rata-rata awal sebesar 33,7 meningkat menjadi 76,00 (siklus I) dan meningkat menjadi 80,0 (siklus II).